Aspartate Embedding Depth Affects pHLIP’s Insertion pKa - Fendos, Justin (2013)
We have used the pHLIP(®) (pH Low Insertion Peptide) peptide family to study the role of aspartate embedding depth in pH-dependent transmembrane peptide insertion. pHLIP binds to the surface of a lipid bilayer as a largely unstructured monomer at neutral pH. When pH is lowered, pHLIP inserts spontaneously across the membrane as a spanning α-helix. pHLIP insertion is reversible when pH is adjusted back to a neutral value. One of the critical events facilitating pHLIP insertion is the protonation of aspartates in the spanning domain of the peptide: the negative side chains of these residues convert to uncharged, polar forms, facilitating insertion by altering the hydrophobicity of the spanning domain. To further examine this protonation mechanism, we created pHLIP sequence variants in which the position of the two spanning aspartates (D14, D25) was moved up or down in the sequence. We hypothesized that aspartate depth in the inserted state would directly affect the proton affinity of the acidic side chains, altering the pKa of pH-dependent insertion. To this end, we also mutated the arginine at position 11 to see if arginine snorkeling modulates the insertion pKa by affecting aspartate depth. Our results indicate both types of mutations change the insertion pKa, supporting the idea that aspartate depth is a participating parameter in determining pH dependence. We also show that pHLIP’s resistance to aggregation can be altered with our mutations, identifying a new criterion for improving pHLIP performance in vivo when targeting acidic disease tissues such as cancer and inflammation.